Phase I Dose‐Escalation Study of Pilaralisib (SAR245408, XL147) in Combination with Paclitaxel and Carboplatin in Patients with Solid Tumors. (April 2017) - Wheler, Jennifer; Mutch, David; Lager, Joanne; Castell, Christelle; Liu, Li; Jiang, Jason; Traynor, Anne M.
Abstract: Lessons Learned: Despite involvement of PI3K pathway activation in tumorigenesis of solid tumors, single‐agent PI3K inhibitors have shown modest clinical activity. Preclinical evidence suggests that combining PI3K pathway inhibitors and chemotherapy can enhance antitumor effects. In patients with solid tumors, the PI3K inhibitor pilaralisib had a favorable safety profile but did not enhance the antitumor activity of paclitaxel plus carboplatin. Further clinical evaluation is warranted to identify effective combination strategies with PI3K pathway inhibitors. Background: Pilaralisib (SAR245408) is an oral, pan‐class I phosphoinositide 3‐kinase (PI3K) inhibitor. This phase I dose‐escalation study evaluated the maximum tolerated dose (MTD), safety, pharmacokinetics (PK), and pharmacodynamics of pilaralisib in capsule and tablet formulations, administered in combination with paclitaxel and carboplatin in patients with advanced solid tumors. Methods: A 3 + 3 design was used. Pilaralisib was administered once daily (QD); paclitaxel (up to 175 mg/m 2 ) and carboplatin (up to area under the curve [AUC] of 6) were administered on day 1 of 21‐day cycles. An MTD expansion cohort of patients with endometrial carcinoma was included. Results: Fifty‐eight patients were enrolled. Six patients (10.3%) had dose‐limiting toxicities, of which only rash (two patients, 3.4%) occurred in more than one patient. The MTD of pilaralisib tablets in combination with paclitaxel and carboplatin was determined to be 200 mg QD. The most frequently reported adverse events (AEs) of any grade were neutropenia (67.2%) and thrombocytopenia (67.2%). PK data showed no interaction between pilaralisib and paclitaxel/carboplatin. Tumor tissue showed moderate inhibition of PI3K and mitogen‐activated protein kinase (MAPK) pathways. Seven of 52 evaluable patients had a partial response (PR; 13.5%). Conclusion: Pilaralisib had a favorable safety profile but did not enhance the antitumor activity of paclitaxel plus carboplatin in solid tumors. The Oncologist 2017;22:377–378